2012
DOI: 10.1371/journal.pone.0040498
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Perturbation Observed in a Hub Network in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease involving the alteration of gene expression at the whole genome level. Genome-wide transcriptional profiling of AD has been conducted by many groups on several relevant brain regions. However, identifying the most critical dys-regulated genes has been challenging. In this work, we addressed this issue by deriving critical genes from perturbed subnetworks. Using a recent microarray dataset on six brain regions, we applied a heaviest induced sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 143 publications
1
49
0
Order By: Relevance
“…Among them, the glucose transport regulator astrocytic phosphoprotein PEA-15 (PEA-15) protein may play a protective role in AD (Ahn et al, 2014) and is able to bind to MAP2K1. MAP2K1 phosphorylation drives cytoplasmic accumulation of heterogeneous nuclear ribonucleoprotein K (HNRPK or HNRNPK) synaptic transmission and spine development regulator protein (Habelhah et al, 2001), whose expression pattern is also correlated with AD progression (Liang et al, 2012).…”
Section: Relationships Of Chronic Cerebral Hypoperfusion Altered Synamentioning
confidence: 99%
“…Among them, the glucose transport regulator astrocytic phosphoprotein PEA-15 (PEA-15) protein may play a protective role in AD (Ahn et al, 2014) and is able to bind to MAP2K1. MAP2K1 phosphorylation drives cytoplasmic accumulation of heterogeneous nuclear ribonucleoprotein K (HNRPK or HNRNPK) synaptic transmission and spine development regulator protein (Habelhah et al, 2001), whose expression pattern is also correlated with AD progression (Liang et al, 2012).…”
Section: Relationships Of Chronic Cerebral Hypoperfusion Altered Synamentioning
confidence: 99%
“…AD is a complex disease, and many factors may affect the gene expression patterns, such as brain region, age as well as the degree of brain destruction (Braak and Braak (B&B) stage). However, several studies have suggested that certain important common features could be shared among different regions in AD brain [29][30][31]. In this study, to investigate the commonality among AD subjects and to obtain stable and consistently differentially expressed genes (CDGs), we used meta-analysis to detect differential expression in nine case-control studies that correspond to different microarray studies (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A relationship has been identified between the cognitive and behavioral symptoms of AD and the dysfunction of certain brain regions (Liang et al, 2008a). A comprehensive study carried out by Liang et al (2012) based the identification of the most critical dysregulated genes in six different AD-relevant brain regions on a sub-graph algorithm. However, this study only analyzed one dataset for each brain region and ignored the large body of research that has focused on one particular brain region.…”
Section: Introductionmentioning
confidence: 99%